Hiện tượng biến động oxi hóa-khử PaNi trong quá trình tổng hợp điện hóa bằng phương pháp CV - Quế và cộng sự, Lê Xuân (Vietnam Journal of Chemistry, 2014)
Polyaniline (PANi) has been electrochemically synthesized on stainless steels electrode in H2SO4 solution using CV technique with maximum polarisation potential Emax = 1.0 V/SCE. During the synthesis 3 couples of PANi redox reactions occur at suitable potentials. The redox reactions have been affected increasing corresponding energy barrier leading to displace forward the characteristic CV peaks according to CV scanning direction. The redox peaks modification has been studied in detail using a variation of peak potentials and currents as a function of CV cycles number. Some redox reactions can be continuously propagated but the others have been degraded during CV polarisation. It is found that at suitable Emax, the disappeared redox peaks can be restored to their sites at nearly original potential. Correlation between redox modification and structure of PANi has been also discussed.